ANALISIS PELUANG USAHATANI CIPLUKAN (Physalis peruviana. L) DI KOTA BENGKULU - Efriza Hardianti; Yossie Yumiati; Herri Fariadi (University of Prof. Dr. Hazairin, SH, 2021)
Ciplukan (Physalis peruviana L.) is a shrub that has many health benefits and has been cultivated and has a high selling value. This study aims to determine how the opportunities for ciplukan farming in Bengkulu City. This study uses primary data and secondary data with interview techniques and questionnaire tools given to people who are considered to know about the opportunities of ciplukan farming in Bengkulu City. The sampling method used in this research was the purposive method and the data were processed using SWOT analysis. The results showed that the opportunity for ciplukan plant farming in Bengkulu City has a great opportunity, namely with a value of 1.55, which means that the ciplukan plant has the opportunity to be cultivated and bred.